2009
DOI: 10.1111/j.1440-1789.2009.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system lymphoma initially mimicking lymphomatosis cerebri: An autopsy case report

Abstract: A 59-year-old immunocompetent man was admitted to our hospital because of progressive dementia with concomitant bilateral uveitis. The first brain MRI revealed diffuse hyperintense lesions in the cerebral white matter of both hemispheres on a T2-weighted image and fluid-attenuated inversion recovery image. However, another MRI taken more than 1 month later revealed enhanced cohesive mass lesions in the bilateral thalami, in addition to the white matter lesions. The white matter lesions were slightly hyperinten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…We also observed that the Cho/Cr ratio of typical, nodular PCNSLs was higher than that of atypical PCNSLs. This may be because homogeneously enhancing PCNSLs had more densely packed lymphoma cells than heterogeneously enhancing PCNSLs, 29 such that they had more active cell division, rapid cell turnover with synthesis of membrane phospholipids, and higher Cho/Cr ratios. The lower Cho/Cr ratios of atypical PCNSLs may result in the decreased diagnostic performance of the Cho/Cr ratio for discriminating between atypical PCNSLs and TDLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that the Cho/Cr ratio of typical, nodular PCNSLs was higher than that of atypical PCNSLs. This may be because homogeneously enhancing PCNSLs had more densely packed lymphoma cells than heterogeneously enhancing PCNSLs, 29 such that they had more active cell division, rapid cell turnover with synthesis of membrane phospholipids, and higher Cho/Cr ratios. The lower Cho/Cr ratios of atypical PCNSLs may result in the decreased diagnostic performance of the Cho/Cr ratio for discriminating between atypical PCNSLs and TDLs.…”
Section: Discussionmentioning
confidence: 99%
“…8,30 An autopsy report of a patient with PCNSL suggested that only scattered infiltration of malignant lymphomatous cells was observed in the nonenhancing tumor portion. 29 Therefore, we speculate that the low cellularity and low invasiveness contributed to the nonspecific MR spectrum in those cases.…”
Section: Discussionmentioning
confidence: 99%
“…From 3238 results, with the earliest paper published in 1950, we winnowed down to 16 articles that met our inclusion criteria of English-language case reports describing dementia as the presenting syndrome in adults with PCNSL. These 16 articles, published between 1990 and 2013, contained 20 original case reports of patients with pathologically confirmed PCNSL: Bakshi et al, 1999; Carlson, 1996; Kanai et al, 2008; Kim et al, 2006; Leschziner et al, 2011; Lewerenz et al, 2007; Matosevic et al, 2010; Nakasu et al, 1990; Pandit et al, 2010; Rollins et al, 2005; Sugie et al, 2009; Sugino et al, 2013; Vital and Sibon, 2007; Weaver et al, 2007; Widdess-Walsh et al, 2005; and Zarabi et al, 1992.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, there have only been 13 pathologically confirmed cases of this type of PCNSL demonstrated by MRI (Table 1). [6][7][8][17][18][19][20][21][22][23] These lesions showed either absent or mild contrast enhancement on MRI. The clinical features were progressive dementia, gait disturbance, and akinetic mutism.…”
Section: Pathological Findingsmentioning
confidence: 99%
“…Malignant cells were rarely found in the CSF or peripheral blood smears. Eight cases could be correctly diagnosed by brain biopsy, [6][7][8][17][18][19]22 three by autopsy, 6,21,23 and the other cases by CSF cytology and/or lymph node biopsy. 8,20 In the present case, brain biopsy was not helpful in making a diagnosis.…”
Section: Pathological Findingsmentioning
confidence: 99%